What Is the True Loss Due to Piracy? Evidence from Microsoft Office in Hong Kong - Leung, Tin Cheuk (The Review of Economics and Statistics, 2013)
Using a unique conjoint data set drawn from 281 college students in Hong Kong, I estimate a random-coefficient discrete choice demand system for Microsoft Office from legal and various illegal sources. Counterfactual results show two things. First, most students would switch to Internet piracy even if the government eradicated street piracy. This explains why software piracy in Hong Kong remains well above 40% despite the government's successful measures to bring down street piracy. Second, the true gain from shutting off all sources of piracy is HK$48.6 (US$6) per person, only 15% of the Business Software Alliance's estimated cost of piracy.